Une caractérisation de l’assurance municipale au Québec - Bernier, Gilles; Gendron, Michel (Assurances)

(untitled) (HEC Montréal, 1987)
The authors present "a characterization of the results of a survey on municipal insurance conducted in early 1986 by the Union of regional county municipalities and local municipalities of Quebec". Tables have been included to illustrate the development of premiums in the area of general public liability and errors and omissions insurance. In light of the results of this survey, the authors have concluded that premium increases over the last three years appear to be justified, if loss ratios are taken into consideration.